The capacity of cargotran sportation along the Northern sea route - E. Gruzdeva (Модернизация, инновация, развитие)
This article reveals the prospects for the development of the Northern sea route taking into account all key factors. It includes analysis of the climatic conditions, the infrastructure, the specific breaker assistance, and the production of Arctic resources, peculiarities of state support and the prevalence of vessels with high ice class. The article applies to methods of qualitative and quantitative analysis. The result is identification of prospects of development of the route mainly as a channel of domestic resource transportation. In addition, the article draws attention to the work of the state Commission on development of the Arctic, which may have a key influence on the development of the Northern sea route.